The prognostic value of YAP1 on clinical outcomes in human cancers - Wu, Ying (Aging (Albany NY), 2019)
Background: As an important downstream factor in the Hippo pathway, yes-associated protein 1(YAP1) has been detected to be elevated in various cancers and demonstrated to play a role in tumor development. Therefore, we evaluated by a meta-analysis the prognostic value of YAP1 in cancer patients. Results: Sixty-eight studies with 8631 patients were identified. The results indicated that YAP1 overexpression predicted unfavorable patient prognosis in studies with overall survival (OS) (HR=1.76, 95%CI: 1.50-2.06, p<0.001) and disease-free survival (DFS) (HR=1.39, 95%CI: 1.22-1.59, p<0.001), as well as in studies with recurrence-free survival (RFS) (HR=2.38, 95%CI: 1.73-3.27, p<0.001), and disease-specific survival (DSS) (HR=2.04, 95%CI: 1.55-2.70, p<0.001). Meanwhile, YAP1 overexpression was also observed to be significantly associated with worse OS in GEPIA (HR=1.2, p<0.001). Conclusions: Overexpression of YAP1 showed great association with poorer prognosis in patients with various cancers, particularly liver cancer. Therefore, YAP1 might be an important prognostic marker and a novel target of cancer therapy. Methods: We searched for potential publications in several online databases and retrieved relevant data. Overall and subgroup analyses were performed. Begg’s and Egger’s tests were used to assess publication bias. Online dataset GEPIA was used to generate the survival curves and verify the prognostic role of YAP1 in patients with tumors.